High-order aberrations: A key factor in accommodative dysfunctions - Gomes, Jessica (2024)
This study investigated the relationship between high-order aberrations (HOAs) and accommodative dysfunctions by analyzing their changes with accommodation. Understanding this relationship is important for understanding the mechanisms underlying these conditions. Sixtythree subjects were divided into five groups: control, infacility of accommodation (INFA), excess of accommodation (EA), insufficiency of accommodation (INSA), and symptomatic without dysfunction (SWD). Variations in root-mean-square (RMS) of the 3rd, 4th, 5th, and 6th orders and HOAs, and fluctuations of RMS HOAs, were measured using a Shack–Hartmann aberrometer at different accommodative stimuli and during residual accommodation after their removal, in the following order: 0.00 D, 1.00 D, 0.00 D, 2.45 D, 0.00 D, 4.73 D and 0.00 D. The SWD group showed a significant increase in RMS HOAs during accommodation and residual accommodation. In contrast, the EA group showed an improvement in the ocular optical quality at higher stimuli. Different patterns of changes in the 3rd, 4th, 5th, and 6th orders were observed across all groups, and fluctuations of RMS HOAs increased significantly in the SWD group during accommodation and residual accommodation. These distinct patterns of aberration changes in different accommodative dysfunctions suggest a potential link between their underlying mechanisms, providing insights that may aid their earlier diagnosis and improved management.